The Diophantine Equation <i>y</i> <sup>2</sup> −<i>k</i> =<i>x</i> <sup>3</sup>

Type: Article

Publication Date: 1914-01-01

Citations: 19

DOI: https://doi.org/10.1112/plms/s2-13.1.60

Locations

  • Proceedings of the London Mathematical Society - View
  • Zenodo (CERN European Organization for Nuclear Research) - View - PDF

Similar Works

Action Title Year Authors
+ The Diophantine Equation <i>y</i> <sup>2</sup> = <i>D</i> <i>x</i> <sup>4</sup> +1 1964 L. J. Mordell
+ The Diophantine Equation <i>y</i> <sup>2</sup> = <i>ax</i> <sup>3</sup> +<i>bx</i> <sup>2</sup> +<i>cx</i> +<i>d</i> 1968 A. Baker
+ PDF Chat The Diophantine Equation <i>x</i> <sup>3</sup> = <i>dy</i> <sup>3</sup> +1 1967 J. H. E. Cohn
+ The Diophantine Equation <i>y</i> <sup>2</sup> = <i>Dx</i> <sup>4</sup> +1 1967 J. H. E. Cohn
+ The Diophantine Equation <i>n</i> ! + 1 = <i>m<sup>2</sup> </i> 1993 Marius Overholt
+ The Diophantine Equation <i>Y</i> (<i>Y</i> + 1)(<i>Y</i> + 2)(<i>Y</i> + 3) = 3<i>X</i> (<i>X</i> + 1)(<i>X</i> + 2)(<i>X</i> + 3) 1975 Tharmambikai Ponnudurai
+ The Diophantine Equations <i>y</i> <sup>2</sup> = <i>x</i> <sup>4</sup> ± 1 in Quadratic Fields 1969 L. J. Mordell
+ On the Diophantine Equation <i>x<sup>3</sup> +y<sup>3</sup> +z<sup>3</sup> </i> = 1 1956 D. H. Lehmer
+ PDF Chat On The Diophantine Equation <i>ay</i> <sup>2</sup> $ <i>by</i> $c = <i>dx</i> <sup>n</sup> 1921 Edmund Landau
Alexander Ostrowski
+ Solutions of the Diophantine Equation: <i>x</i> <sup>3</sup> +<i>y</i> <sup>3</sup> +<i>z</i> <sup>3</sup> =<i>k</i> 1955 J. C. P. Miller
M. F. C. Woollett
+ 100.16 The Diophantine equation <i>n</i>(<i>x</i> + <i>y</i> + <i>z</i>) = <i>xyz</i> 2016 Stan Dolan
+ The Diophantine Equation <i>x</i><sup>2</sup> + <i>y</i><sup><i>m</i></sup> = <i>z</i><sup>2<i>n</i></sup>, Addendum 1990 David W. Boyd
+ The Diophantine Equation <i>x</i><sup>2</sup> + <i>y<sup>m</sup></i> = <i>z</i><sup>2<i>n</i></sup> 1988 David W. Boyd
+ 2015. A note on the diophantine equation <i>z</i><sup>2</sup> = <i>x</i><sup>2</sup> + <i>y</i><sup>2</sup> 1948 R. S. F. Goonewardena
+ On the Diophantine Equation ( <i>x</i> ( <i>x</i> -1)/2) <sup>2</sup> = ( <i>y</i> ( <i>y</i> -1)/2) 1996 Ming Luo
+ Note on Cubic Diophantine Equations <i>z</i> <sup>2</sup> = <i>f</i> (<i>x</i> , <i>y</i> ) with an Infinity of Integral Solutions 1942 L. J. Mordell
+ PDF Chat Correction to: On the Diophantine Equation <i>n</i>(<i>n</i> + <i>d</i>) · · · (<i>n</i> + (<i>k</i> – 1)<i>d</i>) = <i>by<sup>l</sup></i> 2005 Kálmán Győry
Lajos Hajdu
N. Saradha
+ The Diophantine Equation<i>x</i><sup>2</sup>+<i>y</i><sup>2</sup>+<i>z</i><sup>2</sup>=<i>m</i><sup>2</sup> 1962 Robert Spira
+ PDF Chat The diophantine equation<i>Y</i>(<i>Y</i>+ 1)(<i>Y</i>+ 2)(<i>Y</i>+ 3) = 2<i>X</i>(<i>X</i>+ 1)(<i>X</i>+ 2)(<i>X</i>+ 3) 1971 John Cohn
+ On the Diophantine Equation <i>x</i>(<i>x</i>+1)…(<i>x</i>+<i>n</i>-1)=<i>y<sup>k*</sup></i> 1940 L. Louise Johnson

Works Cited by This (0)

Action Title Year Authors